Making LibrariesAccessible for Visually Impaired Users: Practical Advice For Librarians - Devney Hamilton; Burcu Keten (Türk Kütüphaneciliği)
This article provides an introduction to making university libraries accessible to visually impaired users. It includes a summary of how visually impaired students access information and how libraries can provide access to materials, devices and software, and staff support to ensure visually impaired students ’ equal opportunity to use the library. The practical advice for librarians are based on interviews with 18 visually impaired university students and professionals who specialize in media, library services and information retrieval.